Marine natural products. Issue 2 (11th February 2021) - Carroll, Anthony R.; Copp, Brent R.; Davis, Rohan A.; Keyzers, Robert A.; Prinsep, Michèle R.
Abstract : A comprehensive review of 1490 new MNPs including looekeyolides A and B, which are associated with coral black band disease. Abstract : This review covers the literature published in 2019 for marine natural products (MNPs), with 719 citations (701 for the period January to December 2019) referring to compounds isolated from marine microorganisms and phytoplankton, green, brown and red algae, sponges, cnidarians, bryozoans, molluscs, tunicates, echinoderms, mangroves and other intertidal plants and microorganisms. The emphasis is on new compounds (1490 in 440 papers for 2019), together with the relevant biological activities, source organisms and country of origin. Pertinent reviews, biosynthetic studies, first syntheses, and syntheses that led to the revision of structures or stereochemistries, have been included. Methods used to study marine fungi and their chemical diversity have also been discussed.